Cryoprotective effect of low-density lipoproteins on post thaw semen quality in Hariana bull - ANAND, MUKUL; YADAV, SARVAJEET; SINGH, VIJAY; VASWANI, SHALINI; SHUKLA, PANKAJ K (The Indian Journal of Animal Sciences, 2017)
The study aimed to evaluate the cryoprotective effect of low-density lipoprotein in Hariana bull semen. Four adult Hariana bull (3-4 years) after thorough andrological examination were selected for experiment. Semen was collected from each bull twice a week; total of 32 ejaculates (8 from each bull) were collected during the experiment. Collected sample from each bull was divided into 5 equal aliquots. Four aliquots were diluted separately with a Tris-based extender containing different concentration of low-density lipoproteins viz. 7% (T-1), 8% (T-2), 9% (T-3) and 10% (T- 4) as treatment while routinely used extender containing 20% hen egg yolk was used as control (C) to achieve final concentration of 125 million spermatozoa/ml. The diluted samples were cryopreserved and evaluated after 7 days. A significantly higher value of percent live sperms, sperm positive for hypo osmotic swelling test, sperms with intact acrosome and sperms exhibiting pattern F (uncapacitated sperm) were significantly higher in T-3 as compared to other treatment groups and control. The kinematic characters exhibited by sperm i.e forward progression %, VCL (μm/sec), VSL (μm/sec), VAP (μm/sec), Lin (%), Str (%), BCF (Hz) and ALH (μm) were significantly higher in T-3 as compared to other treatment group and control. In conclusion, extender containing 9% low density lipoproteins has better capacity to maintain the sperm character in post thaw Hariana bull semen and can be a preferred concentration to be utilized for cryopreservation with improved conception rate.